PERANCANGAN SISTEM MONITORING JUMLAH SLOT KOSONG PADA GEDUNG PARKIR 3 LANTAI BERBASIS MIKROKONTROLLER - A Asni B; Mayda Waruni Kasrani; Achmad Adi Prayitno (Lembaga Penelitian Universitas Balikpapan, 2021)
Increased use of cars that are not balanced with the provision of adequate parking areas and many drivers who park in any place. The existing parking system only utilizes the parking area and the parking attendant who controls it. Motorists also have to find a place that is free of parking officers or drivers do not pay attention to the parking area, the vehicle owner will look for must get out if you do not get a parking space. To overcome this, make a parking system by using a microcontroller system that facilitates vehicle users to understand the number and arrange an empty parking space. The design of this parking system discusses the available parking system which will be notified via LCD (Liquid Crystal Display) and LED (Light Emitting Diode) at the entrance of the parking lot, and also so that it can be used for the total vehicles in the parking lot with LED indicators ( Light Emitting Diode). This design uses the Arduino Nano as a processor to process data. The servo that translates the bar will be driven. When the parking lot is full, the LCD (Liquid Crystal Display) gives information that there is no vacant land, so the parking user goes up to the next floor. From the Arduino test results, Nano can adjust the circuit well, and Ultrasonic sensors can connect vehicles in each parking area, and the servo bars can be opened and closed again.